IPTEKS STANDAR PELAYANAN PADA PT. TASPEN (PERSERO) CABANG MANADO - Rangian, Melisa Magda; Kumajas, Melisa; Alexander, Stanly W. (Universitas Sam Ratulangi, 2018)
This study aims to see how well PT TASPEN's service in carrying out its duties in managing pension fund savings for employees, is discussed from several factors that exist within PT TASPEN. PT TASPEN is a non-bank financial institution that works to serve pensioners where pension recipients are only for Civil Servants. The author made observations and interviews to find out the discussion of the factors in this study. The applied science and technology method is related to the implementation of community services with analysis techniques through factors in service. Finally the results of the discussion showed that there was still something to be improved at PT TASPEN to further maximize future work. With suggestions in service procedures there must be an increase in the publication of information in print media or mass media, and in the time of service advice for companies that is to add existing teller services and add information boards.Keywords : TASPEN, service, pension fund, civil servant, community